Influence of cognition, premorbid adjustment and psychotic symptoms on psycho-social functioning in first-episode psychosis. (30th August 2016) - Grau, Norma; Rubio-Abadal, Elena; Usall, Judith; Barajas, Ana; Butjosa, Anna; Dolz, Montserrat; Baños, Iris; Sánchez, Bernardo; Rodríguez, Maria José; Peláez, Trinidad; Sammut, Stephanie; Carlson, Janina; et al.
Abstract: Objective: The aim of this study is to evaluate the relationship between psycho-social functioning and symptoms, cognitive function, and premorbid adjustment, in patients with a first-episode psychosis. Method: Clinical data were obtained from 90 patients, who were assessed with the Disability Assessment Scale (DAS-sv), the Positive and Negative Syndrome Scale (PANSS), the Premorbid Adjustment Scale (PAS-S) and with a battery of cognitive tests including Trail Making Tests A and B (TMTA- B), Continous Performance Test (CPT), some subscales of the Wechler Adult Intelligence Scale (WAIS), and the Verbal Learning Test España-Complutense (TAVEC). Results: The results of the study suggest that psycho-social functioning in first-episode psychosis is significantly related to: positive, negative, excitative, affective and disorganized symptoms, social premorbid adjustment, cognitive flexibility, working memory, short term and long term memory. Of these, those which best explained psycho-social functioning are the positive and excitative symptoms, premorbid adjustment, flexibility and memory. Conclusions: These findings highlight the importance early intervention on cognitive and clinical variables to help provide a better psycho-social functioning in people with a first-episode of psychosis. Highlights: ● Social functioning is related to cognition, pre-morbid adjustment and psychotic symptoms. ● Memory functions and flexibility explain social disability in first-episode psychosis. ● Psychological interventions are crucial to achieve satisfactory social functioning.